2017
DOI: 10.7717/peerj.2869
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and correlates of psychological distress among diabetes mellitus adults in the Jilin province in China: a cross-sectional study

Abstract: BackgroundPsychological disorders are common in diabetes mellitus (DM) patients, and the aim of this study was to estimate the prevalence of psychological distress and to determine the influence factors associated with psychological distress among DM patients in the Jilin province of China.Methods and MaterialsMultistage, stratified cluster sampling was used in this cross-sectional study. The 12-item General Health Questionnaire (GHQ-12) was used to assess psychological status with the total score of ≥4 as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
5
20
1
1
Order By: Relevance
“…16 Also, separated and divorced had significantly higher distress in other researches. 4,5 The present study showed a significant association between occupational classes and diabetes related distress (p<0.004). Distress was significantly higher among unemployed (25%) as well as semi-professionals and professionals (21.5%) may be through different mechanisms.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…16 Also, separated and divorced had significantly higher distress in other researches. 4,5 The present study showed a significant association between occupational classes and diabetes related distress (p<0.004). Distress was significantly higher among unemployed (25%) as well as semi-professionals and professionals (21.5%) may be through different mechanisms.…”
Section: Discussionsupporting
confidence: 49%
“…This also favours the risk of serious complications and may reduce the quality of life and lead to early death. 5 Due to emotional burden achievement adequate blood sugar level becomes difficult due to decreased self-management and limited management of self-care activities. Here the distress has more prevalence than depression in a diabetes individual, and other than HbA1c, factors like age, gender treatment adherence and social support also has an influence on the distress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they showed that the risk for type 2 diabetes increased by a hazard ratio (HR) of 1.03 for a one unit increase of the somatization score [19]. As it was mentioned, previous studies showed that psychological problems are common among diabetic patients [9][10][11][12]. It is believed that high prevalence of psychological symptoms among diabetic patients is related to poor glycemic control, diabetes complications, worsened prognosis, and quality of life [34].…”
Section: Discussionmentioning
confidence: 96%
“…Previous evidences suggested that psychological problems are common among diabetic patients, and they are at substantial risk of enhanced depression, anxiety, and stress. It is reported that depressive symptoms are two times more common in patients with diabetes; in addition, they are more susceptible to anxiety symptoms, anxiety disorders, stress reactivity, and psychological distress than population without diabetes [9][10][11][12]. The detrimental effects of these comorbidities in people with diabetes can be seen in a reduced quality of life, an increased risk for micro-and macro-vascular complications, poorer self-care behavior, and early mortality [13].…”
Section: Introductionmentioning
confidence: 99%
“…45 Qiu ve arkadaşlarının 1956 diyabet hastası ile yaptığı bir çalışmada hastaların %26.8'inde ruhsal sıkıntı belirlenmiş ve ruhsal sıkıntının düşük eğitim düzeyi, boşanma/ayrılma, düşük gelir, kısa uyku süresi, hastalığın farkındalığı ve eşlik eden hastalık varlığı ile pozitif yönlü önemli bir ilişki gösterilmiştir. 46 Akılcı olmayan sağlık inançları: Özellikle bazı kültürel gruplarda insülin kullanımına ilişkin akılcı olmayan sağlık inançları yaygındır. Örneğin; diyabet yaygınlığının yüksek olduğu nüfusta bireyler, kronolojik olarak insülin ile eş zamanlı ilerlemiş komplikasyonu olan aile üyelerini görerek insülin ile bu komplikasyonları ilişkilendirebilirler.…”
Section: Komplikasyon Korkusuunclassified